A study on nephropathy in type2 diabetes individuals in coastal Andhra Pradesh, India - Dr. Avapati Raja Sekhar; Dr. Nallamothu Murali Krishna; Dr. Bhaskar Dorapudi; Dr. T Jaya Chandra (International Journal of Medical Research and Review, 2020)
Introduction: Diabetes nephropathy (DN) is an important, life-threatening microvascular complication of diabetes mellitus (DM). With this, a study was conducted to find the association between type 2 DM and DN.Materials and Methods: The study was conducted in the department of general medicine, GSL Medical College. Type 2 diabetic subjects who attended the outpatient and inpatient wards, aged > 30 years were included in the study, known renal disease/ were not considered. Albumin creatinine ratio was measured by immune turbidometry using a microalbuminuria test kit provided by ERBA MANHEIM GERMANY. Serum creatinine was done by creatininase enzymatic method, eGFR was calculated using the CKD-EPI equation. P<0.05 was considered statistically significant.Results: A total of 150 DM participants were included in the study; mean serum creatinine was 1.59 + 1.25 with a range from 0.4 to 8.7 mg/dl and mean eGFR of the study participants was 73.65 + 40.428 ml/min/m2 with a range from 7 to 162 ml/min/m2. DN was detected in 45% (67) participants.Conclusions: The present study reveals that there was significant evidence to support that microalbuminuria or proteinuria in patients with diabetes is a potential risk factor not only for kidney function impairment but also as a marker for high risk of cardiovascular complications.